Construction and application of a liver cancer-targeting drug delivery system based on core–shell gold nanocages - Ji MF (Dove Medical Press, 2018)
Mengfei Ji,1,* Xiaojing Qiu,2,* Lin Hou,1 Shengnan Huang,1 Yuanmin Li,1 Yang Liu,1 Shaofeng Duan,3,4 Yurong Hu1,5 1Henan Key Laboratory of Targeting Therapy and Diagnosis for Critical Diseases, School of Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, People’s Republic of China; 2Henan Eye Institute, Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of China; 3College of Pharmacy, Henan University, Kaifeng, People’s Republic of China; 4Department of Orthopedics, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 5Key Laboratory of Key Technology of Drug Preparation, Ministry of Education, Institute of Drug Discovery & Development, Zhengzhou University, Zhengzhou, People’s Republic of China *These authors contributed equally to this work Background: In order to achieve drug targeting and controlled release, we have successfully developed a novel drug release system DOX/AuNCs-PM-HA with gold nanocages (AuNCs) as photothermal cores, thermally responsive copolymer P(NIPAM-co-Am) (PM) as the near-infrared (NIR) stimuli gatekeeper and hyaluronic acid as a targeting ligand as well as a capping agent. Methods: Cell uptake and cell viability were investigated. In vivo photoacoustic tomography imaging in H22 tumor bearing mice was analyzed for the tumor targeting effect of the nanocomplexes. Antitumor efficacy and the tissue distribution in vivo were investigated.Results: In vitro results demonstrated that the DOX/AuNCs-PM-HA had significant anticancer activity against SMMC-7721 cells under NIR irradiation. Furthermore, in vivo photoacoustic tomography imaging of the nanocomplexes in H22 tumor bearing mice could indicate effective tumor targeting. Our studies on antitumor efficacy and the tissue distribution in vivo showed that many DOX/AuNCs-PM-HA nanocomplexes could efficiently accumulate at the tumor site so that they could inhibit the tumor growth effectively with limited side effects. The in vitro and in vivo results confirmed that the tumor-targeting and controlled-release drug system DOX/AuNCs-PM-HA with the combination of chemotherapy and photothermal therapy showed strong anti-tumor effect and would have great potential for future cancer therapy.Conclusion: This tumor targeting DOX/AuNCs-PM-HA nanocomplex responded not only to the external stimuli of NIR, but also the internal stimuli of hyaluronidase, providing the potential for pinpointed and multi-stimuli responsive intracellular drug release. Keywords: drug delivery, temperature-responsive polymers, hyaluronic acid, chemotherapy, photothermal therapy, photoacoustic imaging